Specialized Financial Intermediaries and the Impact of Savings and Loan Contracts on Real Estate Finance - Manuel Molterer; Julian Amon; Marcel Tyrell (Credit and Capital Markets – Kredit und Kapital, 2023)
Using several different datasets obtained from the German Central Bank (Deutsche Bundesbank) and the German Federal Statistical Office, we provide empirical evidence that savings and loan contracts (SLCs) are a macrosocial phenomenon that smooths housing demand by setting countercyclical incentive structures. Such contracts can thus serve theoretically as important stabilizers of housing (loan) demand. This idiosyncratic characteristic of the German real estate finance market, provided by German building societies ("Bausparkassen"), may also explain the notorious stability of the country's housing market. The significant macroeconomic importance of housing market stability has been prominently highlighted in the context of the 2007/2008 financial crisis, which was triggered by the collapse of the U.S. subprime mortgage market. This research is particularly relevant for countries that experienced fragile housing markets with a high level of cyclicality in demand and nominal house prices.
Keywords: E21; E43; E44; G21; G28; R21; 330; Real estate finance; financial intermediation; housing markets; financial stability; mortgage financing; building societies; savings and loan contracts